Amphipoda living in sponges on the Great Barrier Reef, Australia (Crustacea, Amphipoda) - Myers, Alan A.; George, Anita M. (Zootaxa, 2017)
Fourteen species of amphipod are recorded as endocommensal with the sponges Coelocarteria singaporensis, Coscinoderma mathewsi and Ircinia microconulosa on the Great Barrier Reef. The genus Leucothoe is represented by three new species, one specific to each of the three sponges. Hyperadult males of Aoroides parvus Myers are also described.